Masyarakat Konsumen dalam Kajian Ekonomi Islam - Iwan Setiawan (Al-Ulum, 2020)
This article aims to describe the material needs, welfare, consumer society, and consumption in Islam. The results of the study show that consumption is a very important economic activity in human life. In fulfilling their needs, the consumer society should not only satisfy individual interests (self-interest), but must consider social welfare and benefits. Islam offers a balanced consumption pattern that is neither tabdjir nor ishraf. Consumption in the view of Islam is not merely an activity to meet material needs, but includes the fulfillment of spiritual aspects, namely worship of Allah SWT so that prosperity in the world and the hereafter is achieved. The concept of consumption is full of values, clear and broad goals, principles and ethics. The implication is that consumption activities should be a way and effort to prosper (falah).